1995
DOI: 10.1159/000119228
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Chronic Amphetamine Administration in Local Cerebral Glucose Utilization in Rat

Abstract: The daily dose of amphetamine pretreatment may affect the development of behavioral-sensitized patterns in rodents and amphetamine psychosis in humans. This experiment investigated the regional cerebral metabolic changes in rats after pretreatment with different doses of amphetamine by the 2-[14C] deoxyglucose method. Rates of local cerebral glucose utilization were examined in 37 regions of the rat brain. The result showed generally maximal metabolic augmentation in the 5.0 mg/kg group instead of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The decreased 2-DG uptake after haloperidol administration is thought to result from blockade of dopamine neurotransmission in the striatum [5,10]. This is supported by our previous studies of rats treated with long-term amphetamine, a dopaminergic stimulant [11,12]. In these studies, we found that several regions, especially the dopaminergic system, had elevated 2-DG uptake after long-term amphetamine administration.…”
Section: Discussionsupporting
confidence: 84%
“…The decreased 2-DG uptake after haloperidol administration is thought to result from blockade of dopamine neurotransmission in the striatum [5,10]. This is supported by our previous studies of rats treated with long-term amphetamine, a dopaminergic stimulant [11,12]. In these studies, we found that several regions, especially the dopaminergic system, had elevated 2-DG uptake after long-term amphetamine administration.…”
Section: Discussionsupporting
confidence: 84%
“…The development of sensitization and the testing included 3 stages (Huang et al, 1995(Huang et al, , 1997): In the pretreatment stage, rats were injected intraperitoneally with d-AMPH (1 mg/kg, Sigma Chemical, St. Louis, MO) or saline (control) daily for 2 weeks. Following each injection, rats were placed into one of the three contexts for 120 min before being returned to the home cage.…”
Section: Basic Proceduresmentioning
confidence: 99%
“…This "nonassociative" view, however, fails to explain the result showing a complete lack of behavioral sensitization under some conditions. For example, it has been shown, with 2-deoxyglucose imaging technique, that repeated administrations of AMPH (1 mg/kg) for 14 days, followed by 7 days of abstinence, altered metabolism in many brain areas in response to challenge of AMPH (0.5 mg/kg); however, no behavioral sensitization was observed (Huang et al, 1995(Huang et al, , 1997. This puzzling dissociation between presence of brain change and absence of behavioral expression has now become explainable.…”
mentioning
confidence: 99%
“…The 2-deoxyglucose method can detect regional cerebral metabolic change [3]. By application of this method in this animal model, elevations of local cerebral glucose utilization in the mesolimbic and the nigrostriatal dopaminergic path ways have been shown [4], However, the paradigm used to administer amphetamine is extremely important for studies of sensitization. Chronic amphetamine adminis tration showed general maximal metabolic augmentation in a 5.0-mg/kg group instead of in 1.0-or 10.0-mg/kg groups [4], The timing for the final challenge is also important.…”
Section: Introductionmentioning
confidence: 99%
“…By application of this method in this animal model, elevations of local cerebral glucose utilization in the mesolimbic and the nigrostriatal dopaminergic path ways have been shown [4], However, the paradigm used to administer amphetamine is extremely important for studies of sensitization. Chronic amphetamine adminis tration showed general maximal metabolic augmentation in a 5.0-mg/kg group instead of in 1.0-or 10.0-mg/kg groups [4], The timing for the final challenge is also important. The influence of the withdrawal period on the appearance of behavioral sensitization has been noted previously [5], Behavioral sensitization elicited by re peated administration of amphetamines does not fully develop until a period after discontinuation of the am phetamines, but then persists undiminished for a long time [1,[5][6][7],…”
Section: Introductionmentioning
confidence: 99%